25.2: Invited Paper: Active‐matrix, WVGA GaN Led microdisplay for augmented reality applications. (28th November 2018) - Templier, F.; Dupré, L.; Daami, A.; Renet, S.
Abstract : To meet the growing demand for augmented reality applications, tomorrow's microdisplays will have to offer both high resolution and high brightness (100 times brighter than those of today). Self‐emissive GaN‐based technology can offer outstanding brightness performances. Here we report high resolution (873 x 500), active‐matrix, GaN‐based LED microdisplays with a pixel pitch of 10 µm. They exhibit the highest resolution for the smallest pixel pitch ever reported for GaN microdisplays. High‐density GaN µLED arrays were first patterned at 10‐µm pitch on sapphire substrates. Arrays were then hybridized on CMOS active‐matrix using the microtube technology. Blue and green monochrome prototypes have been realized. Full video, high‐resolution images have been obtained. The performance of these GaN‐based microdisplays make them suitable for a wide range of applications from augmented reality and head‐up displays to pico‐ and compact projectors